Инфернальная мириада Мастера и Маргариты - Глушков, Валерий Александрович; Глушков, Валерій Олександрович; Glushkov, Valerij (My University, 2013)
In the article the particular interpretation of the various philosophical and religious teachings about God and the Devil, described in Mikhail Bulgakov's novel «Master and Margarita». It is concluded that the basis of his interpretation of the role of God and the Devil in the history of mankind put Judaic world view represented by ancient religious texts.
Глушков В. А. Инфернальная мириада Мастера и Маргариты / В. А. Глушков // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 431-448.
Keywords: инфернальная мириада; Мастер и Маргарита; философские учения о Боге; философские учения о дьяволе; религиозные тексты; інфернальна міріада; Мастер та Маргарита; філософські вчення про Бога; філософські вчення про диявола; релігійні тексти; infernal myriad; The Master and Margarita; the philosophical doctrine of God; philosophical doctrines of the devil; religious texts